Design and Multichannel Electromyography System-Based Neural Network Control of a Low-Cost Myoelectric Prosthesis Hand - Siddiq Ahmed, Saygin; Almusawi, Ahmed R.J.; Yilmaz, Bulent; Doǧru, Nuran (Copernicus GmbH, 2021)
This study introduces a new control method for electromyography (EMG) in a prosthetic hand application with a practical design of the whole system. The hand is controlled by a motor (which regulates a significant part of the hand movement) and a microcontroller board, which is responsible for receiving and analyzing signals acquired by a Myoware muscle device. The Myoware device accepts muscle signals and sends them to the controller. The controller interprets the received signals based on the designed artificial neural network. In this design, the muscle signals are read and saved in a MATLAB system file. After neural network program processing by MATLAB, they are then applied online to the prosthetic hand. The obtained signal, i.e., electromyogram, is programmed to control the motion of the prosthetic hand with similar behavior to a real human hand. The designed system is tested on seven individuals at Gaziantep University. Due to the sufficient signal of the Mayo armband compared to Myoware sensors, Mayo armband muscle is applied in the proposed system. The discussed results have been shown to be satisfactory in the final proposed system. This system was a feasible, useful, and cost-effective solution for the handless or amputated individuals. They have used the system in their day-to-day activities that allowed them to move freely, easily, and comfortably. © 2021 Elsevier B.V., All rights reserved.
Keywords: Controllers; Cost Effectiveness; Costs; Matlab; Muscle; Myoelectrically Controlled Prosthetics; Cost-Effective Solutions; Electromyography Systems; Microcontroller Boards; Myoelectric Prosthesis; Neural Network Control; Program Processing; Prosthetic Hands; Received Signals; Neural Networks